Dissecting the Digital World: A Review of the Construction and Constitution of Cyber Conflict Research. Issue 3 (27th February 2018) - Whyte, Christopher
Abstract: Though focused on realizing markedly different analytic outcomes, each of the four books under review here approaches the task of balancing the technological ramifications of advancing digital developments against the implications of relevant sociopolitical context with a reasonable degree of success. Taken together, the books present several significant messages not only about prospects for cyber conflict but also about the aims and imperatives of the burgeoning cyberpolitics research program. In particular, these volumes do a great deal to move the discussion on cyberspace and interstate conflict beyond the bounds of traditional IR theories by demonstrating that the use of assumptions about the predigital world can constrain analytic attempts to understand the parameters of political phenomena in the digital age. Applied too strictly, some assumptions can lead to biased conclusions and overstated predictions, which in turn can have serious policy consequences. Moving forward, IR scholars face the serious task of reevaluating basic conceptual precepts and adapting them to produce new and useful models for understanding conflict, violence, and more.